Effect of Noni Leaves Extract (Morinda citrifolia L.) Supplementation in Feed on Physical Quality of Broiler Breast Meat - Aji Sukoco; Eko Widodo; Imam Thohari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
This research was conducted to know the effect of noni leaves extract (Morinda citrifolia L.) supplementation in feed on physical quality of broiler breast meat such as pH, Water Holding Capacity (WHC), Cooking Loss (CL), and tenderness. Ninety six 8-days old broiler chickens strain Lohmann and of undifferentiated sex (unsexed) were used in this research. The broiler chickens will be reared until 35-days old. The research method was experimental using Completely Randomized Design (CRD) with six treatments and four replications, each replication consisted of four broiler chickens. The treatments consisted of P0 (Basal Feed), P1 (Basal Feed + tetracycline 0.05%), P2 (Basal Feed + noni leaves extract 0.05%), P3 (Basal feed + noni leaves extract 0.1%), P4 (Basal feed + noni leaves extract 0.15%), P5 (Basal feed + noni leaves extract 0.2%). The data were analyzed by ANOVA and continued by Least Significant Difference (LSD) test if there was significantly different result. The results showed that noni leaves extract did not give significant effect (P>0.05) on meat pH, water holding capacity (WHC), cooking loss (CL), and tenderness. However, these results were still acceptable normally such as pH between 5.38-5.57, water holding capacity 34.13-45.64%, cooking loss 33.05-36.97%, but tenderness 16.22-20.57N were less acceptable. The research concluded that supplementation of noni leaves extract (Morinda citrifolia L.) in feed did not increase physical quality of broiler breast meat on pH, Water Holding Capacity (WHC), Cooking Loss (CL), and tenderness.